PENERAPAN METODE UNIFIED APPROACH PADA SISTEM INFORMASI TRAINING RECORD PT. BRIDGESTONE TIRE INDONESIA - Dicky - Hariyanto; Rahmat Tri Yunandar; Lily Ciptaningrum (Evolusi : Jurnal Sains dan Manajemen, 2020)
To support the workers get effectiveness and efficiency in their job at the company, normally a company facilitating the development of job training for employees being creative, how to think, how to act, knowledge, skills, and work ethic. The training record system currently in use at PT Bridgestone Tire Indonesia (BSIN) can still work, but less efficient because there are some things that can not be accessed on the page. For the examples, anyone who has been training on the theme to be searched, and when retrieving data from training record into Excel is very messy. For this reason, this journal is written to discuss the design of training record information systems that will renew the appearance of the training record pages that already existed and will cover pre-existing deficiencies. The design of this information system is a solution to the existing problem, and with the design of this new information system the company activities related to the training record can run effectively, efficiently, and smoothly